2019
DOI: 10.1038/s41398-019-0595-2
|View full text |Cite
|
Sign up to set email alerts
|

Depression and suicide risk prediction models using blood-derived multi-omics data

Abstract: More than 300 million people worldwide experience depression; annually, ~800,000 people die by suicide. Unfortunately, conventional interview-based diagnosis is insufficient to accurately predict a psychiatric status. We developed machine learning models to predict depression and suicide risk using blood methylome and transcriptome data from 56 suicide attempters (SAs), 39 patients with major depressive disorder (MDD), and 87 healthy controls. Our random forest classifiers showed accuracies of 92.6% in disting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 37 publications
1
62
0
Order By: Relevance
“…To solve this problem, many works have been done to identify potential biomarkers for MDD patients with SI. 10–13 Our previous study found that the extrinsic coagulation pathway might be a biomarker for suicidal behavior in MDD. 11 Some researchers proposed that the neural representations or health records could be used to build the depression and suicide risk prediction models.…”
Section: Introductionmentioning
confidence: 97%
“…To solve this problem, many works have been done to identify potential biomarkers for MDD patients with SI. 10–13 Our previous study found that the extrinsic coagulation pathway might be a biomarker for suicidal behavior in MDD. 11 Some researchers proposed that the neural representations or health records could be used to build the depression and suicide risk prediction models.…”
Section: Introductionmentioning
confidence: 97%
“…In this context, reducing the burden of MDD is vital. This is achievable through the application of accurate risk prediction tools, which could enable the early identification of individuals more prone to the development of MDD [5]. For instance, alexithymia, a trait characterized by the difficulty of identifying feelings and emotions and by lack of motivation, may be considered a risk factor for the development of MDD, as well as suicide attempts [6].…”
Section: Introductionmentioning
confidence: 99%
“…Overall, our model evaluations provide a more reliable and conservative measure of ML performance compared with prior studies (Bhak et al, 2019; Guilloux et al, 2015; Khodayari‐Rostamabad, Reilly, Hasey, Debruin, & Maccrimmon, 2010; Yi et al, 2012; Yu et al, 2016). Specifically, previously published studies perform feature selection, often through DEG analysis, and training of the ML classifier based on the set of preselected features, on the same dataset (Bhak et al, 2019; Yi et al, 2012).…”
Section: Discussionmentioning
confidence: 70%
“…Yu, Xue, Redei, and Bagheri (2016) applied an SVM approach to classify MDD cases and controls based on expression data of preselected blood RNA markers, measured using quantitative real-time polymerase chain reaction. Recently, a study by Bhak et al (2019) utilized a multi-omics approach. A random forest classifier was applied on blood transcriptomic and methylomic data, combined, to distinguish between MDD cases, suicide attempters, and controls.…”
Section: Introductionmentioning
confidence: 99%